2019
DOI: 10.3390/su11092494
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Consumption Changes across China’s Provinces Using A Spatial Shift-Share Decomposition Model

Abstract: China’s growing electricity consumption has become an important factor to improving socio-economic development, as well as aggravating environmental degradation. Based on the provincial level data in China for the entire period and every five years during 2000–2015, this paper used a spatial shift-share analysis (SSS) to detect the driving factors of electricity consumption changes in China, mainly focusing on the spatial spillover effects of electricity consumption which have been ignored by previous literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The existence of regional differences had already been shown in the analyzed literature [20,21,35], and, in general, the scholars showed that the standardized economic model is prone to accentuating territorial differences in terms of economic growth and employment, without the intervention of the public sector. For this reason, the EU, aware of this situation, has been developing and implementing mechanisms, generally of a budgetary nature-as is the case of the European Funds-to reduce these differences.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The existence of regional differences had already been shown in the analyzed literature [20,21,35], and, in general, the scholars showed that the standardized economic model is prone to accentuating territorial differences in terms of economic growth and employment, without the intervention of the public sector. For this reason, the EU, aware of this situation, has been developing and implementing mechanisms, generally of a budgetary nature-as is the case of the European Funds-to reduce these differences.…”
Section: Discussionmentioning
confidence: 92%
“…Analyzing the existing literature, it was detected that the authors frequently use the so-called shift-share analysis in this type of studies. Among the main contributions using this methodology are the studies of [20][21][22][23][24][25][26]. Additional studies were conducted specifically by implementing the shift-share analysis in the energy sector of Asiatic [20,22,27] and European countries [22,28].…”
Section: Regional Analysis Of the Impact Of Renewable Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, using statistical data to express the spatiotemporal dynamics of EC in rural areas is still a big challenge. Nighttime light data have shown certain advantages in simulating urbanization [57,58], economy [59,60], population distribution [50,61,62], the effects of war [63,64], poverty distribution [65,66], PM2.5 pollution [52], electric consumption [67,68], and other aspects of human geography. Furthermore, the results of our study were in consistence with previous studies [24,47].…”
Section: A Nighttime Light Data Provide a New Perspective For Simulamentioning
confidence: 99%
“…China's rapid economic development in the last 20 years has resulted in increased demand for electricity and ensuing shortages in electric power supply [7]. China's growing EPC has become an important factor to improving socio-economic development, as well as aggravating environmental degradation [8]. EPC is one of the basic indices for evaluating electric power use [9].…”
Section: Introductionmentioning
confidence: 99%